The Athens Mobile γ-Spectrometry System (AMESOS) - Karailias, A.; Lagaki, V.; Katsiva, C.; Kanellakopoulos, A.; Mertzimekis, T. J.; Kafantaris, F. C.; Godelitsas, A. (HNPS Advances in Nuclear Physics, 2019)
We report on a new mobile γ-spectrometry system (AMESOS) developed at the University of Athens. The system aims at carrying out in situ measurements to study distributions of NORM and TENORM at harsh environments or where sampling is difficult. AMESOS has been characterized by using standard calibration sources and minerals of known, independently determined, U and Th concentrations. Simulations of the system have been performed with MCNP and Geant4. As a proof of good field operation, AMESOS was deployed in a series of measurements at Mt. Kithaeron, near Athens, extending earlier data and estimating absorbed dose rates that concern the public.